EVALUASI DEPURASI TOTAL BAKTERI PADA KERANG DARAH DARI PERAIRAN DESA SUKAL, KABUPATEN BANGKA BARAT - Pratiwi, Fika Dewi; Sari, Eka (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2019)
Blood clams cultured in Sukal Village West Bangka Regency sell in the market around Bangka Belitung Island Province. These blood clams often sell without sanitary and hygiene control treatment during cultivation or post-harvest. For that reason, the clams have the potential for pathogenic bacterial contamination that can harm the consumer's health. The study aimed to analyze the initial content of total bacteria (total plate count) in blood clam sample collected from Sukal Village and analyze the content of total bacteria (TPC) after depuration treatment for 24 hours and 48 hours. The depuration experiment followed the recirculating system for 24 hours and 48 hours. The UV light used to irradiate the natural saline water and chitosan from shrimp shell used as a filter and antibacterial agent. The temperature and salinity were constant at 29 o C and 30 o/oo. Total plate count (TPC) method used in this research according to SNI 01-2332.3-2006, while ISO 4833-1: 2013; PerKa BPOM No. 16 used as the quality standard of total bacteria content in blood clam. The result found that the blood clams collected from the first station contained total bacteria exceeded the established quality standards. Independent T-test showed that there was no significant difference between the reduction in the TPC content of blood clam samples with a depuration time of 24 hours and a time of 48 hours.Â